Kedisiplinan dalam Keluarga Kristen terhadap Kepribadian Siswa SMPN 7 Kota Bogor - Supinah, Supinah; Gurning, Lasmauli (Sekolah Tinggi Teologi Kadesi Bogor, 2024)
The problem of junior high school student misconduct has become a major concern in various regions, including both large and small cities. This misconduct encompasses various negative behaviors such as fights, alcohol and drug use, theft, and more. Even though they may not be directly involved, Christian parents are worried about the future of their children. This research highlights the role of Christian parents in educating and shaping the personality of students. Based on Biblical principles, as outlined in Deuteronomy 6:6-9 and Ephesians 6:4, parents have a primary responsibility in the spiritual education of their children. Without discipline, students will lack a strong moral compass. Through observations of Christian students at SMP Negeri 07 Bogor, this research identifies several issues related to discipline and student personality. The research method used is quantitative with purpose sampling technique, involving data collection through questionnaires, interviews, and direct observation. The findings highlight the importance of discipline in shaping students' personalities who fear God. The disciplinary methods used include authoritarian, permissive, and democratic approaches, aimed at producing responsible students who adhere to Christian teachings.